The Influence of Governance on Cyber Supply Chain Performance with Mediating Effect from Cyber Supply Chain Visibility - Wong Norissa Leticia Atmajaya; Yonathan Palumian (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This research aims to analyze the influence of governance on Cyber Supply Chain (CSC) Performance, which is mediated by Cyber Supply Chain (CSC) Visibility to achieve effective and efficient cyber supply chain risk management (CSCRM) practices for the supply chain management (SCM) process. The population of this research is all manufacturing companies on the island of Java, Indonesia, that have used computerized systems in their supply chain processes with qualifications or certifications ISO 27001, ISO 28000, ISO 28001, or other certifications that are management information system standards. This research will reveal the strengths or weaknesses of the mediating role of CSC Visibility on CSC Performance in manufacturing companies. This study also found empirical evidence that having a dedicated governance team consisting of technical and non-technical personnel is important in CSCRM in the manufacturing industry, especially Java Island in Indonesia.